POSISI UNDANG-UNDANG PERLINDUNGAN KONSUMEN NOMOR 8 TAHUN 1999 DALAM UPAYA PERLINDUNGAN TERHADAP KONSUMEN - Njatrijani, Rinitami (Fakultas Hukum, Universitas Diponegoro, 2017)
Since the enactment of UUPK No.8 Year 1999 which has been going on for 17 years in its implementation still faced many obstacles caused by many factors. Some of these factors include some mistakes, deficiencies and weakness seatings in the UUPK itself is related to grammar, systematic, business actors responsibility, consumer dispute resolution and institutional. Therefore the need for changes to the purpose of improving the UUPK, in accordance with the initial purpose of the establishment of this law is to protect consumers in Indonesia. It should be questioned how the position of UUPK No.8 Year 1999 in the effort to protect the consumer. Keywords : Position, UUPK No. 8 Year 1999, Consumer Protection